THE IMPACT OF RAKIJA CULTURAL HERITAGE AND RAKIJA MARKETING ON THE CONSUMER PURCHASING DECISIONS - Slobodan Adžić; Marko Pavlović; Marijana Milunović; Đorđe Pavlović; Tijana Savić Tot; Pavle Radanov (Ekonomika Poljoprivrede (1979), 2024)
This is the first study on the tradition and cultural heritage of the rakija market based on consumer behavior analysis. The primary objective is to investigate the impact of cultural tradition on consumer behavior regarding the purchase of rakija, the national alcoholic beverage of Serbia. The secondary objective of this research is to measure the magnitude to which the marketing program of distilleries influences consumers’ purchases of rakija. The research data were collected in Serbia from December 2023 to March 2024 utilizing a survey approach. Electronic data collection was carried out through an online questionnaire. The study sample comprised 608 valid respondents (n=608) who were chosen randomly. Traditional cultural heritage affects the purchase of rakija; however, the UNESCO recognition of šljivovica as part of its intangible heritage list does not. Moreover, the marketing program of distilleries affects the purchase of rakija. However, the effect sizes of these phenomena are insignificant.